Cultural Heritage Property Disputes In International Arbitration Proceedings - Mskhvilidze, Tamar (Alternative Dispute Resolution Yearbook, 2024)
The article's purpose is to argue why arbitration is beneficial for users despite the availability of a wide range of alternative dispute resolution (ADR) means to the parties involved in cultural heritage disputes. While litigation is a time-consuming, expensive, and public process, arbitration offers a speedy and confidential alternative. This offers more flexibility and control over the results than litigation. The tension between investor rights and cultural heritage protection raises several questions. Is the measure implemented by the state justified by the fact that it aims to protect cultural heritage? Can governments use cultural policies to discourage investment or discriminate against foreign investors? It is important to clarify the extent to which arbitral tribunals pay attention to cultural heritage and how they balance the rights of the investor and the cultural policies of the host state.